Towards Educator 4.0: technology competency-based teaching - Melor Masdoki; Rosseni Din; Mohd Effendi @ Ewan Mohd Matore (Penerbit Universiti Kebangsaan Malaysia, 2024)
Educator 4.0 is a new concept that describes the characteristics of future educators capable of handling and implementing various smart technologies into their teaching methods and strategies. Since the education system has rapidly changed due to the digital and smart technology transformation, educators especially in Higher Learning Institutions are required to upgrade their teaching skills and become more competent to meet the needs of the new generations of students. There is not much discussion on Educator 4.0 and how it can be measured. This is also due to the limited literature globally, thus there is a need to develop new instruments and models to measure the 4.0 Educators’ competency. The theories of Technology Literacy and DigCompEdu were adapted to develop this new instrument model. Factors and constructs such as Technologyy 4.0 literacy, Technology 4.0 resources, and student empowerment were identified and used to measure the level of 4.0 competencies among the educators. The data from the respondents in Pre-University Institutions, represented by Kolej MARA and Kolej Profesional MARA lecturers on the east coast of Malaysia, was collected using a non-probability sampling method combined with convenience sampling. A PLS-SEM approach was used to validate this new instrument model. The findings reveal that the instruments developed were valid and all constructs have a positive contribution towards Educator 4.0 competency. All constructs were good at measuring the Educator 4.0 competency. The findings of the study will provide a better understanding of educators’ 4.0 competency regarding the context of the study. Besides, this study will enrich the literature on 4.0 Educators’ competency.